Pelatihan Pemanfaatan Pekarangan Dengan Budidaya Tanaman Hortikultura Menggunakan Wick Irrigation System Untuk Mendukung Ketahanan Pangan di Desa Wonopringgo Kabupaten Pekalongan - Farchan Mushaf Al Ramadhani; Ari Handriatni; Heri Ariadi; Bony Samego; Putri Isti Amalia (Journal of Community Development, 2024)
Food security is a condition where household food is met, which is reflected in the availability of sufficient food, both in quantity and quality, safe, equitable, and affordable. The potential of yards is huge in increasing household food security. However, in Wonopringgo Village, the people do not use their yards optimally. Therefore, training related to the use of horticultural cultivation in the yard using a wick irrigation system is essential. This community service aims to raise awareness of the Wonopringgo Village community in general and the Wonopringgo Village Women's Farmers Group (KWT) in particular so that they can utilize their yards by cultivating horticultural plants using a wick irrigation system. The methods used in this service activity are investigation, preparation, action, and reflection. The results of this activity showed that the participants' knowledge about cultivating plants using a wick irrigation system increased significantly. Participants' interest in utilizing the yard by cultivating horticultural plants using a wick irrigation system also increased after the training. Overall, this service activity had a significant positive impact on participants in terms of increasing knowledge and interest in utilizing yards by cultivating horticultural plants using a wick irrigation system. This shows that training like this can be a practical and sustainable solution to support household food security, especially in areas with limited water or urban areas.